The impact of relapse definition and measures of durability on MS clinical trial outcomes. (April 2023) - Satyanarayan, Sammita; Cutter, Gary; Krieger, Stephen; Cofield, Stacey; Wolinsky, Jerry S; Lublin, Fred
Background: Definitions of trial measures are consequential to accurately capturing outcomes and cross-trial comparability, particularly for derivative measures. Objective: Using CombiRx, examine the impact of relapse definition on endpoints and evaluate the durability of progression measures in Relapsing Remitting Multiple Sclerosis (RRMS). Methods: CombiRx relapse types were distinguished by the presence or timing of Expanded Disability Status Scale (EDSS) increase. Using the broadest definition of relapse, progression endpoints were assessed in patients without relapses on trial. Durability compared EDSS at study end and time of worsening. Results: Broadening relapse definition to the most inclusive definition increased annualized relapse rate (ARR) threefold in all arms and decreased progression independent of relapse activity (PIRA), defined as 6-month confirmed disability worsening (6M CDW) without relapse, by 44%. Neither PIRA nor PIA (progression independent of any inflammatory activity) guaranteed durable worsening, with 43% and 40%, respectively, improving by end of study. Multivariate analysis showed two CDW events, not relapse, predicted durability among patients meeting 6M CDW. Conclusions: The stringency of relapse definition impacted absolute ARR and composite endpoints in RRMS. Despite the most generous relapse definition, 43% of patients meeting PIRA on trial did not have durable worsening suggesting that relapse definition and durability should be considered to avoid overestimating progression in RRMS trials.